2009
DOI: 10.1111/j.1462-2920.2009.01924.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the lethal fish egg parasite Ichthyodinium chabelardi as a member of Marine Alveolate Group I

Abstract: Cells of the parasitic, unicellular eukaryote Ichthyodinium chabelardi were isolated from eggs of sardine (Sardina pilchardus) and from a previously unrecognized host, bogue (Boops boops), off the Atlantic coast of Portugal. Immediately after release from the infected fish egg or newly hatched larva, I. chabelardi cells were spherical and non-motile. After few minutes, spherical cells became flagellated and motile. Following 2-3 days of incubation and several divisions, spherical flagellated cells developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
0
22
1
Order By: Relevance
“…For the first time, mass fish mortality from this parasite was observed when the studies were con ducted on the Mediterranean coast of Algeria [3,4]. Our knowledge of Ichthyodinium biology and geo graphical distribution is much replenished in recent years [1,[5][6][7][8][9]11], but there is still no comprehensive description of its life cycle. I. chabelardi development can be divided into two parts.…”
mentioning
confidence: 98%
“…For the first time, mass fish mortality from this parasite was observed when the studies were con ducted on the Mediterranean coast of Algeria [3,4]. Our knowledge of Ichthyodinium biology and geo graphical distribution is much replenished in recent years [1,[5][6][7][8][9]11], but there is still no comprehensive description of its life cycle. I. chabelardi development can be divided into two parts.…”
mentioning
confidence: 98%
“…Based on data currently available in GenBank, there are 204 rRNA sequences from syndinean taxa described to at least the genus level, mostly from the genera Hematodinium (176 sequences) (35,42) and Amoebophrya (22 sequences) (18,25), with a few sequences attributed to Duboscquella (2 sequences) (12a, 20), Ichthyodinium (12 sequences) (41,48), and Syndinium (40). Syndinean group I was shown to contain species of both Ichthyodinium, parasites of fish eggs, and Duboscquella, parasites most often described as isolated from tintinnid ciliates.…”
mentioning
confidence: 99%
“…More recent analyses based on molecular phylogeny show that Syndiniales are not typical dinoflagellates but instead constitute a sister group to these (Skovgaard et al 2005). However, the grouping of Ichthyodinium within Syndiniales may also be incorrect, since it is associated with a second sister group to the typical dinoflagellates, the so-called marine alveolate Group I (Skovgaard et al 2009). Hence, 3 genetically distinct groups of dinoflagellatelike organisms seem to exist, even though the exact relationship between these groups is still a matter of debate (Guillou et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that European and Asian isolates of Ichthyodinium spp. represent 2 different phylotypes (Skovgaard et al 2009). Despite the ubiquitous occurrence of I. chabelardi, its life cycle and route of infection are still not completely understood.…”
Section: Introductionmentioning
confidence: 99%